Transcriptome analysis of regeneration during Xenopus laevis experimental twinning - Sosa, Eric A. (Int J Dev Biol, 2019)
Animal embryos have the remarkable property of self-organization. Over 125 years ago, Hans Driesch separated the two blastomeres of sea urchin embryos and obtained twins, in what was the foundation of experimental embryology. Since then, embryonic twinning has been obtained experimentally in many animals. In a recent study we developed bisection methods that generate identical twins reliably from Xenopus blastula embryos. In the present study we investigated the transcriptome of regenerating half-embryos after sagittal and dorsal-ventral (D-V) bisections. Individual embryos were operated at midblastula (stage 8) with an eyelash hair and cultured until early gastrula (stage 10.5) or late gastrula (stage 12) and the transcriptome of both halves analyzed by RNA-seq. Since many genes are activated by wound healing in Xenopus embryos, we resorted to stringent sequence analyses and identified genes up-regulated in identical twins but not in either dorsal or ventral fragments. At early gastrula cell division-related transcripts such as histones were elevated, whereas at late gastrula pluripotency genes (such as sox2) and germ layer determination genes (such as eomesodermin, ripply2 and activin receptor ACVRI) were identified. Among the down-regulated transcripts, sizzled, a regulator of Chordin stability, was prominent. These findings are consistent with a model in which cell division is required to heal damage, while maintaining pluripotency to allow formation of the organizer with a displacement of 90° from its original site. The extensive transcriptomic data presented here provides a valuable resource for data mining of gene expression during early vertebrate development.